The Value of Nursing Research. (May 2020) - Ives Erickson, Jeanette; Pappas, Sharon
Abstract : Innovations in patient care, nursing, and the practice environment are hallmarks of organizations receiving American Nurses Credentialing Center (ANCC) Magnet Recognition ® . In this month's "Magnet ® Perspectives" column, the chair and vice-chair of ANCC's Commission on Magnet Recognition examine the growing importance of nursing research on patient care and outcomes and the role of Magnet hospitals as research pacesetters for the nursing profession. The authors discuss the critical difference between research and evidence-based practice, why both are important, and how organizations can develop the structures and processes to inspire and advance a robust culture of clinical inquiry.